Oxidative addition of organic halides on palladium(0) complexes stabilized by dimethylfumarate and quinoline-based N–P or N–S spectator ligands. (14th December 2015) - Canovese, Luciano; Visentin, Fabiano; Biz, Chiara; Scattolin, Thomas; Santo, Claudio; Bertolasi, Valerio
Graphical abstract: Six Pd(0) complexes stabilized by the olefin dimethylfumarate and bidentate ligands based on the quinoline frame were synthesized, characterized and reacted with four different aryl and alkyl halides. The ensuing reactivities were assessed and the solid state structures of one starting complex and of one reaction product have been resolved. Abstract: We have studied the oxidative addition of some organic halides on palladium(0) dimethylfumarate complexes bearing heteroditopic (N–P or N–S) quinoline-based spectator ligands from the experimental and theoretical point of view. We have measured the half-life of some oxidative addition reactions carried out in two different solvents (CD2 Cl2 and CD3 CN). The reactions were studied under mild conditions by NMR and the reactivities of different oxidants towards the complexes under study were compared. The rates of reaction were influenced by the nature of the spectator ligands and the solvent. The thioquinoline derivatives display a higher reactivity than that of the phosphoquinoline complexes and in general the reaction rates are higher in CD3 CN than in CD2 Cl2, although such a behavior is not always observed. We propose a plausible mechanism for the oxidative reaction in different solvents based on the experimental results and an adequate computational approach. Finally, the solid state structures of two reaction products were resolved and reported.